PENGEMBANGAN EKONOMI: USAHA MEMBERDAYAKAN PELAKU EKONOMI KECIL DAN MENENGAH - SAID, ZAINAL (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
Raising public participation was very limited due to two things: frst, due to the limited ability to control resources that enable participation in progress and the unavailability of mechanisms for participation due to a closed system. Second, the limited resources allocated to the public does not allow them to participate actively, both in the economic as well as social and political. Similarly, in the case of a social system that does not provide ï¬exibility in accommodating community involvement. The approach used is a qualitative approach because it examines the meaning of economic businesses which have not yet received of various government policies. So small or marginalized position masyasrakat received less attention in the market rotation resulting inequality is so obvious. Community development should start from the siding, which is a way of life and express the preferences of the community itself to prioritize the planned changes will be made. Society has a world of cognitive, evaluative world in the form of values and norms, symbolic world that need to be studied to gain an understanding of what is important and what is not considered important by the community. In this way penmbangunan process will lead to a match between the programs with the needs of specifc communities.